Pharmacokinetic profile and metabolite identification of bornyl caffeate and caffeic acid in rats by high performance liquid chromatography coupled with mass spectrometry. Issue 7 (30th January 2019) - Shi, Baimei; Yang, Lingjian; Gao, Tian; Ma, Cuicui; Li, Qiannan; Nan, Yefei; Wang, Shixiang; Xiao, Chaoni; Jia, Pu; Zheng, Xiaohui
Abstract : We revealed the metabolic profile of bornyl caffeate by HPLC-Q-TOF/MS, and then simultaneously examined the pharmacokinetics of bornyl caffeate and CA after administration of a single dose of bornyl caffeate by HPLC ion trap MS. Abstract : Bornyl caffeate was initially discovered as a bioactive compound in medicinal plants. Despite the promising pharmacological activities including anti-tumor and antibacterial activities, the pharmacokinetics of the compound remain open. This work developed a high performance liquid chromatography-tandem mass spectrometric method for the determination of bornyl caffeate and caffeic acid (major metabolite and a main unit of bornyl caffeate) in vivo . Successful application of the method included identification of its metabolites and investigation on the drug pharmacokinetics. A total of 30 compounds were identified as the metabolites of bornyl caffeate in rats. We attributed these metabolites to phase I metabolic routes of reduction, oxidation, hydrolysis and phase II metabolic reactions of glucuronidation, sulfation, O -methylation and glycine. Glucuronidation, sulfation, O -methylation and reduction were the main metabolic pathways of bornyl caffeate. The method presented a linear range of 1–4000 ng mL −1 . The pharmacokinetic profile of bornyl caffeate was found to be a three compartment open model, while caffeic acid fitted to a two compartment open model when it was administered alone or served as the main metabolite of bornyl caffeate. The time to peak concentration ( T max ) and the maximum plasma concentration ( C max ) of bornyl caffeate were 0.53 h and 409.33 ng mL −1 . Compared with original caffeic acid, the compound displayed an increased half-life of elimination ( T 1/2β ), area under the concentration time curve from 0 to t (AUC0– t ) and area under the concentration time curve from 0 to ∞ (AUC0–∞ ), a decreased half-life of absorption ( T 1/2α ) and an identical C max . Taking together, we concluded that bornyl caffeate is able to rapidly initiate therapeutic effect and last for a relatively long time in rats; metabolic pathways of O -methylation and reduction is key to interpret the mechanism and toxicity of bornyl caffeate.